Feline Heartworm in Clinical Settings in a High Canine Prevalence Area - Alberigi, Bruno; Campos, Diefrey Ribeiro; Branco, Aline Serricella; Bendas, Alexandre; Brum, Rodrigo Pereira; Calixto, Raquel; Alves, Leucio Câmara; Pinheiro Júnior, Jose Wilton; Knackfuss, Fabiana Batalha; Labarthe, Norma; Levy, Julie K.; Mendes-de-Almeida, Flavya (Frontiers in Veterinary Science, 2022)
Heartworm (HTW) infection in cats is associated with persistent pulmonary pathology, even when clinical signs are absent. Treatment options for cats are limited once infected, making prevention an important topic for discussion with cat owners. In Brazil, tests to detect feline HTW infections are unavailable, likely leading to an underestimation of its impact on the wellbeing of cats. The present study investigated the seroprevalence of HTW antigen in cats living in an area with high canine HTW prevalence and investigated risk factors and clinical signs associated with HTW disease in cats from Rio de Janeiro, Brazil. Clinical examinations were conducted, and serological evaluations performed with a point-of-care test (SNAP® Feline Triple® Test, IDEXX Laboratories, Inc.). A total of 586 cats were examined. The HTW antigen seroprevalence was 1.2%. Heartworm positive results were significantly associated with vomiting and abnormal lung sounds. Results from this study indicate that cats residing in areas of high canine HTW prevalence should have HTW disease as a differential diagnosis when presenting with compatible clinical signs. Veterinarians should prioritize client education and promote regular use of effective prophylaxis to protect feline health.